Captive : my time as a prisoner of the Taliban - Van Dyk, Jere (Times Books : Henry Holt and Co., 2010)
An American reporter's chilling account of being kidnapped and imprisoned by the Taliban, in the no-man's-land between Afghanistan and Pakistan.